The Effectiveness of Pair Work Strategy in Improving Students’ Speaking Abilities of Eight Graders Through Role-Play in Factual Recount Text - Ramadhan Annisya Nur Ozalia; Fauzia Nur (SUJANA: Education and Learning Review, 2026)
English occupies a central role as the most widely used international language, particularly in speaking contexts; however, many Indonesian EFL students continue to encounter difficulties in engaging in meaningful spoken communication. This study investigates the effectiveness of pair work and role-play as collaborative pedagogical strategies for improving students' speaking abilities in factual recount text at the junior high school level. A quantitative quasi-experimental design was employed, involving 60 eighth-grade students divided equally into a control group and an experimental group. The control group received conventional instruction, while the experimental group was taught through pair work combined with role-play activities. Data were collected via pre-test and post-test assessments evaluated using a speaking rubric adapted from Brown (2004). The findings indicated a statistically significant improvement in the experimental group, with an independent sample t-test value of p = .000 and a large effect size (η² = 0.801). The post-test mean score of the experimental group reached 78.93, substantially exceeding the control group's post-test mean of 51.07. These results suggest that pair work and role-play foster active learner engagement, promote authentic interaction, and reduce speaking anxiety, thereby producing measurable gains in oral proficiency. It is recommended that teachers incorporate pair work and role-play as regular instructional strategies in EFL speaking classes.